Predictive value of pan-immune-inflammation value in the prognosis of adults with status epilepticus: a retrospective study - Fu, Jie; Chu, Yifei; Zhao, Chenxin; Peng, Lilei (Frontiers in Aging Neuroscience, 2025)
ObjectiveTo investigate the predictive capacity of the pan-immune-inflammation value (PIV) for functional outcomes in patients with status epilepticus (SE).MethodsIn this study, we investigated and confirmed the prognostic significance of PIV in adult patients with SE. Clinical information and laboratory test data of the patients were extracted. We gathered the information on 30-day mortality following SE and used the modified Rankin scale (mRS) to assess functional prognosis. Multivariable logistic regression models were employed to assess the relationship between PIV and SE prognosis. Additionally, receiver operating characteristic (ROC) curve analysis was conducted to identify the optimal PIV threshold for predicting poor outcomes of SE patients.ResultsInitially, the discovery cohort comprising 132 SE patients were examined. The findings revealed that 18.2% (24/132) of patients died within a 30-day period post-SE, and 25.8% (23/89) experienced unfavorable prognosis during the 6-month follow-up period. Multivariate logistic regression analysis showed that higher PIV on admission was independently related to poor 6-month prognosis of SE patients (odds ratio: 1.002; 95% confidence interval, 1.000–1.004; p = 0.026). ROC analysis determined 1,090 as the optimal cutoff value of PIV for predicting poor 6-month prognosis in these patients. Moreover, multivariate logistic regression analysis of the external cohort demonstrated that PIV ≥ 1,090 was an independent predictor for poor SE outcome (odds ratio: 42.433; 95% confidence interval, 1.456–1236.343; p = 0.029), which verified our findings.ConclusionHigher PIV is strongly correlated with an elevated risk of unfavorable SE prognosis. Our results suggest that PIV is a simple and reliable predictor for SE prognosis.